Aerodynamic loads on a fixed wind turbine blade with gurney flap - Bacchi, Federico (2014)
This work presents a description of the numerical analysis and results, particularly the aerodynamic forces and moments on a fixed wind turbine blade with and without a "Gurney flap” of 2 % chord height, located just below the blade trailing edge. At the present stage it is of interest to model a fixed blade in the turbine starting position, and to compare the aerodynamic forces and starting torque obtained with and without the Gurney flap. Along- and cross-wind forces will also be measured in wind tunnel experiments, which will allow validating the numerical simulation.